2012
DOI: 10.1371/journal.pntd.0001613
|View full text |Cite
|
Sign up to set email alerts
|

Additive Protection by Antioxidant and Apoptosis-Inhibiting Effects on Mosquito Cells with Dengue 2 Virus Infection

Abstract: Cytopathic effects (CPEs) in mosquito cells are generally trivial compared to those that occur in mammalian cells, which usually end up undergoing apoptosis during dengue virus (DENV) infection. However, oxidative stress was detected in both types of infected cells. Despite this, the survival of mosquito cells benefits from the upregulation of genes related to antioxidant defense, such as glutathione S transferase (GST). A second defense system, i.e., consisting of antiapoptotic effects, was also shown to play… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 44 publications
0
35
0
Order By: Relevance
“…[31][32][33] It is therefore of relevance to determine if VEEV infection will impact insect cells and lead to accumulation of ROS in a similar manner as we observed in U87MG cells. We studied whether infection of mosquito cells with TC-83 would lead to a disruption of mitochondrial function.…”
Section: Veev Infection Results In Loss Of Mitochondrial Membrane Potmentioning
confidence: 71%
See 1 more Smart Citation
“…[31][32][33] It is therefore of relevance to determine if VEEV infection will impact insect cells and lead to accumulation of ROS in a similar manner as we observed in U87MG cells. We studied whether infection of mosquito cells with TC-83 would lead to a disruption of mitochondrial function.…”
Section: Veev Infection Results In Loss Of Mitochondrial Membrane Potmentioning
confidence: 71%
“…It has been demonstrated that in the case of flavivirus infections, infected insect cells show changes in antioxidant mechanisms that decrease the extent of cell death. [31][32][33] It has been demonstrated for Dengue virus that infected mosquito cells mounted a stronger antioxidant response by synthesising antioxidant enzymes (elevation of Glutathione S-transferase activity). 48 Mitochondrial distribution in cells and mitochondrial mobility are essential features of healthy cells.…”
Section: Discussionmentioning
confidence: 99%
“…Staining for cleaved caspase 3 was first noted at 48 hpi in these cells and was evident at later times points, too; however, only rare mosquito cells were TUNEL positive from 72–120 hpi, indicating that widespread frank apoptosis was not induced. Although we have not investigated these findings, the lack of apoptosis in ZIKV-infected C6/36 cells may be related to upregulation of inhibitor of apoptosis (IAP) genes which have been shown to be operative in Dengue 2 virus-infected C6/36 cells (43) or, perhaps, through inhibition of a molecule downstream of caspase-3 within the apoptosis pathway. Further studies into ZIKV infection and the apoptotic pathway in mosquito cells are required to better understand the role of caspase activation and cell death.…”
Section: Discussionmentioning
confidence: 94%
“…Flaviviruses are thought to exploit the cellular stress response to aid replication [51] and oxidative stress is thought to aid the replication of positive-strand RNA viruses [52]. Further, it has been proposed that the balance between antioxidant responses maintains an anti-apoptotic environment during flavivirus infection of the cell [53, 54], presumably facilitating virus replication and transmission.…”
Section: Discussionmentioning
confidence: 99%